Heterosis in ridge gourd (Luffa Acutangula (Robx.) L.) - Thankachan Julie Mole (Department of Olericulture, College of Horticulture, 2000)
The present investigation on Heterosis in Ridge gourd [Luffa acutangula (Roxb.) L] was conducted at the Vegetable Research Farm, College of Horticulture, Thrissur during 1999-2000. From the germplasm available in the Department of Olericulture, five parents belonging to different genetic clusters were selected. They were crossed in a diallel fashion to produce F 1 hybrids. The FI's without reciprocals were grown in a randomised block design. These F, hybrids were evaluated along with their parents to derive information on general and specific combining ability. From combining ability analysis, it was noticed that the parental lines LA 81 and LA 87 were good combiners for yield. The best comination for yield was LA 81 x LA 44 and that for earliness was LA 43 x LA 44. The best combination for average fruit weight and fruit length was LA 87 x LA 86. The combination LA 44 x LA 87 had maximum duration which also exhibited maximum vine length. The standard heterosis was highest for LA 43 x LA 44 for earliness. The maximum heterosis for yield was exhibited by the combination LA 81 x LA 44 which also showed increased fruit number per plant. The combination LA 81 x LA 44 showed increased fruit girth which also showed more number of fruits per plant hence increased yield. But length of fruit was maximum for the combination LA 87 x LA 86 but fruits produced by this cross was less. The study revealed that the three hybrids viz. LA 81 x LA 44, LA 87 x LA 86 and LA 43 x LA 44 are promising hybrids showing superiority in yield and its component characters considered in the study.